Journalism for social change in Asia : reporting human rights - Downman, Scott; Ubayasiri, Kasun (London : Palgrave Macmillan, 2017)
This book explores the role and purpose of journalism to spark and propagate change by investigating human rights journalism and its capacity to inform, educate and activate change. Downman and Ubayasiri maximize this approach by proposing a new paradigm of reporting through the use of human-focussed news values. This approach is a radical departure from the traditional style that typically builds on abstract concepts. The book will explore human rights journalism through the lens of complex issues such as human trafficking and people smuggling in the Asian context. This is not just a book for journalists, or journalism academics, but a book for activists, human rights advocates or anyone who believes in the power of journalism to change the world.
Introduction to journalism for social change -- Human rights as a news value -- Human rights journalism and the new journalism ecosystem -- Human trafficking, people smuggling, refugee migration and the news media -- Smuggled or trafficked : the story of the Rohingya -- Human rights reporting, war crimes and refugee migration -- Reporting human trafficking -- Best practice models for reporting human rights -- Media, human rights and corporate social responsibility.
Includes bibliographical references and index.
Keywords: Journalism -- Asia; Human rights in mass media; Journalism; Asia